Future scenarios for electronic training in Saudi universities - Alruhaimi, Tahani Ayed; Alharthi, Manal Trekhem; Almohanna, Noura Ibrahim; Altuwaijri, Fatemah Abdalaziz (Journal of Educational and Psychological Sciences, 2025)
The current study aimed to build future scenarios for e-training in Saudi universities through the following: identifying the reality of e-training in Saudi universities and identifying the most important challenges of e-training in Saudi universities. To achieve the objectives of the study and answer its questions, the study used the descriptive method in the style of document analysis, the descriptive method in the style of social survey, and the forward-looking method in the style of scenarios. The study yielded a number of result the electronic results indicated that real training is represented at three levels: the preparation level, the implementation level, and the evaluation level. The challenges facing electronic training in Saudi universities on the point of view of experts are summarized as follows: challenges related to the humanitarian element, and material challenges. A group of experts has presented proposals to maximize electronic training in Saudi universities It was clear that there was a need to develop organized institutional efforts, in addition to material and human support to achieve the required improvements, as the following scenarios have been developed: ⁠Exploration scenarios that depend on the current situation and presented several alternatives for the future, and targeting scenarios that depend on future goals.